SSB Pruned DFT-Spread FBMC Signal With Low PAPR in Direct-Detection PONs - Xiaoling Zhang; Chongfu Zhang; Mingyue Zhu; Wei Jin; Chen Chen; Xiang Gao; Kun Qiu (IEEE Photonics Journal, 2020)
Filter bank multi-carrier (FBMC) using offset quadrature amplitude modulation (OQAM) has recently attracted increasing interests for the next-generation high-speed optical transmission systems, due to the salient FBMC modulation advantages in terms of high spectrum efficiency by completely removing the cyclic prefix. However, high peak-to-average power ratio (PAPR) still plays a key role of constraining the performance of FBMC systems. In this paper, we investigate a single sideband (SSB) pruned discrete Fourier transform (DFT)-spread FBMC for direct-detection (DD) passive optical network systems (PONs). It is demonstrated that the PAPR of the SSB pruned DFT-spread FBMC signal with the overlapping factor of 1.56 outperforms the conventional FBMC signal and the simple DFT-spread FBMC signal by ~2 dB and 1 dB at the complementary cumulative distribution function (CCDF) of 1 × 10-3, respectively. Finally, by using the pruned DFT-spread FBMC with low PAPR, the aggregate data rate of 50-Gbit/s can be achieved after 50-km single mode fiber (SMF) transmission below the 7% hard decision forward-error correction (HD-FEC) threshold in the DD PONs.